OPTIMIZING THE IMPACT OF LEARNING ENVIRONMENT ON STUDENT ACHIEVEMENT: THE MEDIATING ROLE OF INTERPERSONAL COMMUNICATION SKILLS - Mohammad Fuadi Rifqi; Farij Ibadil Maula (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: The utilization gap in educational facilities is a crucial issue in higher education, where the availability of adequate learning environments often does not correlate linearly with improvements in student academic achievement. Purpose: This study aims to investigate the causal mechanism of the learning environment's influence on student achievement by examining the role of interpersonal communication skills as a mediating variable. Novelty: The novelty of this study lies in the empirical evidence of the vital role of communication soft skills in bridging the relationship between physical facilities and academic performance, which has often been considered directly related. Research Methods: Using an explanatory quantitative design, this study involved a census population of 192 Office Administration Education students at Surabaya State University. Data were analyzed using Structural Equation Modeling (SEM-PLS). Results: The test results show that the learning environment does not have a significant direct effect on student achievement. However, the learning environment has been proven to have a significant positive effect on communication skills, which in turn has a significant impact on achievement. Path analysis confirms that interpersonal communication skills act as a full mediator. Research Contributions: This study implies that the existence of physical facilities and a conducive campus environment is not enough to boost academic achievement without effective communication activities. Therefore, higher education institutions must shift their strategy from merely providing infrastructure to designing interactive learning methods that require student collaboration to optimize learning outcomes